Chronic Q fever: An ongoing challenge in diagnosis and management - Ira Das; Nicola Guest; Richard Steeds; Peter Hewins (Canadian Journal of Infectious Diseases and Medical Microbiology)
Chronic Q fever is a potentially fatal disease. The current difficulty in the diagnosis of this condition is discussed in the present article. A 51-year-old woman with a history of aortic valve replacement presented with complaints of feeling generally unwell, pyrexia and occasional unproductive cough over a period of several weeks. Phase 1 immunoglobulin G titre to Coxiella burnetii was initially detected at a low level (1:320, detected using immunofluorescence) and was not considered to be significant according to the modified Duke criteria. Later in the course of her illness, the patient’s antibody titre rose to a high level (1:1280). The issues regarding current laboratory diagnosis and management of Q fever are discussed. Chronic Q fever can be associated with an inadequate serological response. Close follow-up of cases is essential. The recommended serological criteria for the diagnosis of Q fever endocarditis needs to be revisited.